Dark feet and dark wings: penetrating the depths of the Earth - Zeiger, Robin B. (Journal of analytical psychology, 2022)
The author, although an analyst, is an initiate into the topic of environmental destruction. Following Wendell Berry, she enters the dark and begins a journey of dream‐like reflection, weaving images from her own dream and drawing on the work of Vaughan, Bernstein, Soloveitchik and Sacks. She asks, ‘not if but where does climate change enter the room?’. The second half of the paper focuses on the manifestations of environmental destruction in dreams and sandplay from three patients and one dream group participant. The paper argues that the analyst must see and intuit before our patients can access the objective layer of environmental destruction in dreams and symbolic material. In this way, the climate becomes the wounded patient, and the analyst as wounded healer must first access his/her own relationship to the wounds inside. Finally, using an ancient Jewish mythological story of Rabbi Shimon bar Yochai, the author argues that Jungian analysts must work to find balance between the inner world of depth psychology and the outer world with its challenges and problems that include environmental destruction. L’auteur, bien qu’étant analyste, est une initiée du sujet de la destruction de l’environnement. Inspirée par Wendell Berry, elle entre dans le noir et commence un voyage de réflexion en tissant des images provenant de son propre rêve et utilisant les travaux de Vaughan, Bernstein, Soloveitchik et Sacks. Pour elle la question est non pas si mais où est‐ce que le changement climatique entre dans la pièce ? La deuxième moitié de l’article s’intéresse aux manifestations de destruction de l’environnement dans les rêves et la thérapie par le jeu de sable de trois patients et d’une personne participant à un groupe de rêves. L’article soutient que l’analyste doit voir et suivre son intuition avant que les patients aient accès à la couche objective de la destruction de l’environnement dans les rêves et le matériel symbolique. De cette manière, le climat devient le patient blessé, et l’analyste, en tant que guérisseur blessé, doit tout d’abord accéder à sa propre relation aux blessures intérieures. Enfin, s’appuyant sur une ancienne histoire mythologique Juive, celle de Rabbi Shimon bar Yochai ‐ qui se retira dans une caverne pendant 13 années ‐ l’auteur soutient que les analystes Jungiens doivent œuvrer à trouver l’équilibre entre le monde intérieur de la psychologie des profondeurs et le monde extérieur avec ses défis et ses problèmes, qui incluent la destruction de l’environnement. Die Autorin, zugleich Analytikerin, ist eine Eingeweihte das Thema Umweltzerstörung betreffend. Wendell Berry folgend betritt sie die Dunkelheit und beginnt eine Reise der Reflexion indem sie Bilder aus ihrem eigenen Traum webt und sich auf die Arbeit von Vaughan, Bernstein, Soloveitchik und Sacks stützt. Sie fragt: 'Nicht ob, sondern wo kommt der Klimawandel in den Raum?' Die zweite Hälfte der Arbeit konzentriert sich auf Manifestationen der Umweltzerstörung in Träumen und Sandspielen von drei Patienten und einem Traumgruppenteilnehmer. Im Text wird argumentiert, daß der Analytiker sehen und intuitiv sein muß, bevor unsere Patienten auf die objektive Schicht der Umweltzerstörung in Träumen und symbolischem Material zugreifen können. Auf diese Weise wird das Klima zum verwundeten Patienten und der Analytiker, als verwundeter Heiler, muß zuerst auf seine eigene Beziehung zu den Wunden im Inneren zugreifen. Schließlich wird, unter Verwendung einer alten jüdischen mythologischen Geschichte von Rabbi Shimon bar Yochai, der sich 13 Jahre lang in eine Höhle zurückzog, argumentiert, daß Jungianische Analytiker daran arbeiten müssen, ein Gleichgewicht zwischen der inneren Welt der Tiefenpsychologie und der äußeren Welt mit ihren Herausforderungen und Problemen zu finden, was die Umweltzerstörung einschließt. L'Autore, sebbene analista, è un novizio al tema della distruzione ambientale. Seguendo Wendell Berry, entra nell'oscurità e inizia un viaggio di riflessione tessendo immagini dal proprio sogno e attingendo al lavoro di Vaughan, Bernstein, Soloveitchik e Sacks. Si chiede: "non se, ma dove entra nella stanza il cambiamento climatico?" La seconda metà del documento si concentra sulle manifestazioni di distruzione ambientale nei sogni e nel gioco della sabbia di tre pazienti e un partecipante al gruppo dei sogni. L'articolo sostiene che l'analista deve vedere e intuire prima che i nostri pazienti possano accedere allo strato oggettivo di distruzione ambientale nei sogni e nel materiale simbolico. In questo modo il clima diventa il paziente ferito, e l'analista come guaritore ferito deve prima accedere alla propria relazione con le ferite interne. Infine, utilizzando un'antica storia mitologica ebraica del rabbino Shimon bar Yochai, che si ritirò in una grotta per 13 anni, sostiene che gli analisti junghiani devono lavorare per trovare l'equilibrio tra il mondo interiore della psicologia del profondo e il mondo esterno con le sue sfide e problemi che includono la distruzione ambientale. Хотя автор является аналитиком, она озабочена проблемой разрушения окружающей среды. Вслед за Уэнделлом Берри она вступает в темноту и начинает путешествие размышлений, переплетая образы своего собственного сновидения и данные работ Вогана, Бернстайна, Соловейчика и Сакса. Она спрашивает: "Не если, а где изменение климата входит к нам?" Вторая половина статьи посвящена проявлениям разрушения окружающей среды в сновидениях и песочных композициях трех пациентов и одного участника сновидческой группы. В статье утверждается, что аналитик должен обладать видением и интуицией, чтобы наши пациенты могли получить доступ к объективному слою разрушения окружающей среды в своих сновидениях и символическом материале. Таким образом, климат становится раненым пациентом, а аналитик, будучи раненым целителем, должен вначале получить доступ к своим собственным отношениям с внутренними ранами. Наконец, используя древний иудейский миф о рабби Шимоне бар Йохае, который уединился в пещере на 13 лет, она утверждает, что юнгианские аналитики должны работать над тем, чтобы найти баланс между внутренним миром глубинной психологии и внешним миром с его вызовами и проблемами, которые включают разрушение окружающей среды. La autora, es analista, y también iniciada en el tópico de la destrucción medioambiental. Siguiendo a Wendell Berry, ella entra en la oscuridad y comienza una travesía reflexiva hilvanando imágenes de sus propios sueños y apoyándose en los trabajos de Vaughan, Bernstein, Soloveitchik y Sacks. Ella pregunta, ‘¿sino dónde el cambio climático entra en la sala? La segunda parte del trabajo se focaliza en manifestaciones de la destrucción del medioambiente en sueños y en la caja de arena de tres pacientes y de un participante de un grupo de sueños. El trabajo argumenta que el/la analista debe poder ver e intuir antes que nuestros pacientes puedan acceder la dimensión objetiva de la destrucción medioambiental en sueños y material simbólico. De este modo, el clima deviene el/la paciente herido, y el/la analista como curador herido debe primero poder acceder su propia relación con su herida interior. Finalmente, utilizando una antigua historia mitológica de la tradición Judía del Rabino Shimon bar Yochai, quien se retiró a una cueva durante trece años, ella argumenta que analistas Junguianos deben trabajar para encontrar un balance entre el mundo interno de la psicología profunda y el mundo externo con sus desafíos y problemas como el de la destrucción ambiental. 黑脚和黑翼:穿透地球的深处。 作者虽然是一位分析师, 但却是环境破坏这一主题的发起者。继温德尔‐贝里之后, 她进入了黑暗, 开始了反思之旅, 从她自己的梦境中编织图像, 并借鉴了沃恩、伯恩斯坦、索洛维契克和萨克斯的作品。她问道:"不是如果, 而是气候变化在哪里进入房间?"论文的后半部分集中于三个病人和一个梦境小组参与者的梦境和沙盘游戏中环境破坏的表现。本文认为, 在我们的病人能够进入梦境和象征性材料中的环境破坏的客观层之前, 分析师必须看到和直觉到这部分。这样一来, 气候变成了受伤的病人, 而作为受伤的治疗者的分析师必须首先与他/她自己的内部伤口建立联系。最后, 她讲了一个古老的犹太神话故事, 这是一个关于拉比西蒙约凯在一个山洞里隐居了13年的故事, 借用这个故事, 她提出, 荣格分析师必须努力在深度心理学的内在世界, 和处于挑战和困难, 包括环境破坏的外部世界之间找到平衡。